Efektivitas Kurikulum Kewirausahaan di Perguruan Tinggi Swasta dalam Membangun Jiwa Bisnis Mahasiswa: Tinjauan Literatur dan Strategi Pengembangan - Mahesa Vicky Satria Ramadhan Lihu; Muhammad Zainuddin (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The implementation of entrepreneurship curricula in higher education institutions, particularly private universities, continues to face various multidimensional challenges. Based on a review of the literature, these challenges include pedagogical aspects, infrastructure, policy frameworks, and linkages with industry. The predominance of theoretical learning approaches results in students having limited opportunities to gain practical experience in applying entrepreneurial concepts in real-world contexts. In addition, limited partnerships with industry restrict students’ access to authentic business experiences, mentorship, and broader market networks. Supporting infrastructure for entrepreneurship, such as business incubators and access to funding, remains insufficient, while higher education regulations and internal institutional policies have not been fully flexible or consistent in accommodating the dynamic nature of entrepreneurship. This study aims to analyze the alignment of the Entrepreneurship Semester Learning Plan (Rencana Pembelajaran Semester/RPS) at Universitas Sari Mulia with national curriculum standards based on Graduate Learning Outcomes (Capaian Pembelajaran Lulusan/CPL), to evaluate the structure of the RPS document, and to examine the integration of Merdeka Belajar Kampus Merdeka (MBKM) activities into the entrepreneurship RPS. This research employs a descriptive qualitative method using a literature review approach and a limited case study, complemented by in-depth purposive interviews with five active students who have completed the entrepreneurship course. The findings indicate that the Entrepreneurship RPS at Universitas Sari Mulia meets national curriculum standards and demonstrates a well-structured design in terms of CPL, Course Learning Outcomes (CPMK), and active learning methods. However, aspects related to learning evaluation, academic references, and the integration of MBKM activities still require further improvement.